Nursing Care Model Based on Knowledge Management in Preventing Nosocomial Infection After Caesarean Section in Hospital - Ahsan Ahsan (Jurnal Ners, 2014)
Introduction: Nosocomial infection is one indicator of the quality of health services in the community, which also determines the image of health care institutions becauseit was a major cause of morbidityand death rate (mortality) in hospital. Nursing care based on knowledge management is established from identification knowledge which is required, prevention performance of nosocomial infections post section caesarea. Nosocomial infections component consists of wound culture result.Method: This study was an observational study with a quasi experimental design. The population was all of nursing staff who working in obstetrics installation in hospitals A and B as much as 46 people. Sample was the total population. Data was collected through questionnaire, observation sheets and examination of the wound culture. Data was analyzed using t test B 1.274 dan p=0.028Result: The result showed that 1) there was difference in knowledge management implementation before and after training; 2) there was difference in nurse’s performance in preventing nosocomial infection before and after training; 3) there is significant relationship between nurse’s performance in preventing nosocomial infection and infection incidence; 4) there is no significant difference of nursing care impementation on nosocomial incidence.Discussion: In conclusion, the development of nursing care based on knowledge management as a synthesis or induction of findings directed at 1) nurses’ knowledge does not affect the performance of the prevention of nosocomial infections; 2) knowledge management has a positive effect on the performance of the prevention of nosocomial infections; 3) implementation of infection prevention is integrated capabilities between knowledge, skills and attitudes of nurses in implementing performance in care.